Importance of Enhanced Surveillance for Prevention of Pertussis in Children. Issue 7 (July 2015) - Domínguez, Angela; Godoy, Pere; Toledo, Diana; Soldevila, Núria; García-Cenoz, Manuel; Farrús, Gloria; Crespo, Inma; Caylà, Joan A.; Sala, Maria Rosa; Camps, Neus; Barrabeig, Irene; Alvarez, Josep
Abstract : Background: Bordetella pertussis infection causes considerable morbidity, even in countries with high vaccination coverage. Surveillance of pertussis is usually passive and based on mandatory reporting. We assessed the epidemiologic and clinical characteristics of pertussis cases detected by passive or enhanced surveillance. Methods: A prospective population-based study was carried out from January 2012 to December 2013 in Catalonia and Navarre, 2 Spanish regions with a total population of 8.2 million. For each confirmed case, variables of age, sex, clinical symptoms, laboratory results and vaccination status were investigated. Associations between the variables studied and the type of surveillance were assessed by odds ratio (OR) and its 95% confidence interval (CI). Logistic regression was used to estimate adjusted OR (aOR). Results: In children <18 years of age, passive surveillance was the most important source of detection (95.7% in <1 year). In children 5–10 years of age, passive surveillance detected 67.5% of cases. In those ≥18 years, enhanced surveillance was the most frequent source of case detection (82.5%). Inspiratory whoop (aOR: 1.94; 95% CI: 1.40–2.70), apnea (aOR: 1.92; 95% CI: 1.28–2.87) and posttussive vomiting (aOR: 1.43; 95% CI: 1.04–1.96) were symptoms included in the clinical case definition that were associated with passive surveillance. Conclusions: Underreporting of symptomatic cases is important not only in adults, but also in children >1 year of age and suggests that providing clinics with free, fast laboratory diagnostic tests, together with enhanced surveillance of family contacts of any age is necessary to better determine existing cases. Enhanced surveillance may be helpful to better understand transmission patterns in the family and in the community.